ANTESENDEN PROMOSI DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMILIHAN PERGURUAN TINGGI SWASTA YANG DIMEDIASI CITRA MEREK - I Gusti Ngurah Satria Wijaya; Annisa Rizky Nirmala; Putu Febby Aldora (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Higher education is a source of innovation and solutions for the growth and development of the nation as time goes by. One of the important issues in higher education is the decline in the number of new students entering private universities, influenced by the Covid-19 pandemic and the change of several state universities to become state universities with legal entities. This causes competition between private universities to become increasingly fierce, which cannot be avoided. This research aims to analyze the influence of promotion on the decision to choose a private university in Bali with the brand image variable as the mediating variable. The data used in this research is primary data originating from questionnaires distributed to students at the STIKOM Bali Institute of Technology and Business. The analysis technique used in this research is structural equation model (SEM) analysis. The results of this research are that promotion and brand image partially have a positive and significant effect on the decision to select private universities and promotion has a positive and significant effect on the brand image of private universities. For indirect effects, promotion has a positive and significant indirect effect on PT selection decisions which is mediated by brand image.